Mewujudkan Efektifitas dan Efisiensi Tata Kelola di Usaha Mikro melalui Pelatihan Manajemen Operasional dan Sumber Daya Manusia - Kurniawan, Dhika Amalia; Nurfadila, Agustin Rani; Nurfattah, Arizqiya; Djayusman, Royyan Ramdhani; Mahfudz, Akhmad Affandi (Jurnal PKM Manajemen Bisnis, 2025)
The contribution of MSMEs is significant to Indonesia's economic growth, but many MSME actors still rely on simple and poorly organized work methods in operational and human resource management. This results in poor production efficiency and entrepreneurial activities. A similar thing also happened at UM Krecek Krupuk Bu Nor, which is engaged in traditional snacks. Efficiency in production and sales activities is not optimal due to the lack of operational management and human resources. This training aims to provide assistance and training in operational governance and human resources, which can positively impact business actors. The method used is focused on interactive and participatory training with several stages such as preparation, implementation, and monitoring. The results of this training have a positive impact on UM Krecek Krupuk Bu Nor in operational and human resource management and can increase the level of efficiency in entrepreneurial operations.